Colonial Architecture in Lebanon From the Nineteenth Century Until the Middle of the Twentieth Century - مخائيل سلوى; صقر علي (Latakia University Journal -Engineering Sciences Series, 2021)
The Levant region was affected by the various civilizations that it passed through, and played a role in its economic, political and social development. Lebanon is part of that region that was subjected to the Ottoman and French occupation during the nineteenth and twentieth centuries, where the world witnessed during that period global developments and events Such as the industrial revolution and colonialism, which played a role in the development of architecture and urbanism and created new building styles and methods. The research deals with the study of the effects of colonialism on the architectural output in Lebanon, known as the “State of Greater Lebanon” at the time, through historical, analytical studies and critically descriptive study of the country’s architecture and identifying the prevailing local and European architectural styles, to emphasize the depth of those influences and the investigation of architectural styles Innovative and changes in architecture.